The law of international organisations - White, Nigel D., 1961- (Manchester : Manchester University Press, 2017)
"This book provides a concise account of the principles and norms of international law applicable to the main-type of international organisation - the inter-governmental organisation (IGO). That law consists of principles and rules found in the founding documents of IGOs along with applicable principles and rules of international law. The book also identifies and analyses the law produced by IGOs, applied by them and, occasionally, enforced by them. There is a concentration upon the United Nations, as the paradigmatic IGO, not only upon the UN organisation headquartered in New York, but on other IGOs in the UN system (the specialised agencies such as the World Health Organisation)."--
Inter-governmental organisations -- Membership, voting and funding -- Legal character of the constituent treaty -- International legal personality : the key to autonomy -- The doctrine of powers : the key to governance -- Institutional lawmaking : a new source of international law? -- Sanctions -- Military measures -- Responsibility of international organisations -- Accountability, access to justice and remedies.
Includes bibliographical references and index.
Keywords: International agencies -- Law and legislation; International agencies -- Law and legislation